La discordance linguistique. L'intervenant et le patient ne parlent pas la même langue ou ne peuvent pas communiquer adéquatement [infographie] - Consortium national de formation en santé (2022)

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

Gaps in knowledge and practices of malaria prevention in Francophone African immigrants in Metropolitan Edmonton - Hanna, Taylor A.; Ahmed, Ali; Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Youssef; Petrick, Ryland; Vincent, Etienne; El Hafid, Mélanie; Hawkes, Michel T.; Ravi, Srilata; Gnidehou, Sedami (Malaria Journal, 2022)
Background Important knowledge gaps exist in the understanding of the management of the risks of imported malaria in Canada among Francophone immigrants from sub-Saharan Africa (FISSA). The aim of this cross-sectional study was to investigate the malaria related-knowledge, attitude and practices (KAP) of FISSA in Edmonton, where these immigrants are in an official minority language situation and the impact of language barriers on these factors. Methods A structured survey was used to examine the KAP of 382 FISSA in the Edmonton area from 2018 to 2019. Fisher’s Exact Test was applied to determine if there were associations between knowledge of malaria and different risk factors. Results Almost all FISSA (97%) had an accurate knowledge of fever as the key symptom of malaria. Interestingly, 60% of participants identified bed nets as a preventive method and only 19% of participants had accurate knowledge of malaria transmission. An accurate knowledge of symptoms was significantly associated with a high perceived risk of contracting malaria [odds ratio (OR) 4.33, 95% confidence interval (CI) 1.07–20.62]. Furthermore, even though 70% of FISSA had a high perceived risk of contracting malaria in endemic regions, only 52% of travellers had a pre-travel medical encounter. Importantly, language was not the predominant reason for not seeking pre-travel medical advice, although 84% of respondents chose French as their official language of preference when seeking medical advice. Having a French-speaking physician was correlated with satisfactory prevention knowledge (OR 1.96, 95% CI 1.16–3.35). With respect to health-seeking behaviour, 88% of respondents with a child < 5 years of age would seek medical care for fever in the child after travel to sub-Saharan Africa (SSA). Conclusion This study highlights that factors other than knowledge, risk assessment, and language might determine the lack of compliance with pre-travel medical encounters. It underscores the need for effective strategies to improve this adherence in minority settings.

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Les expériences de patients francophones qui se présentent fréquemment à l'urgence pour des raison de santé mentale - Vandyk, Amanda; Lightfoot, Sophie; Levesque, Kristine; Domecq, Marie-Cécile.; Jacob, Jean Daniel (Recherche en soins infirmiers, 2022)
Introduction: Language and communication are pivotal to the safe care and management of people with mental health disorders, particularly when these patients are linguistic minorities. Objectives/method: To explore these experiences within linguistic minority populations by completing a literature review and qualitative interviews. Interviews were conducted in Ottawa, Canada, with francophone patients. The studies included in the review represented the international literature on linguistic minorities in general. Results: Overall, the experiences described in the published articles were similar to the participants' own experiences, suggesting that barriers to care exist even in settings mandated to provide services in both official languages. Discussion/conclusion: There are many barriers to the provision of mental health care services, regardless of the dominant language. However, we identified an internalized sense of responsibility felt by linguistic minority patients, who feel compelled to compensate for or fill in the language gaps of providers. Keywords: health services accessibility; language; mental health; qualitative research; rapid review.